Student critical thinking objectivism - JOHN IRWIN (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The goals of this research are to (1) gain a better understanding of what college students mean when they refer to CT, (2) determine whether or not CT can be taught, and (3) determine what approaches would be most effective.Method: Undergraduates studied in a second-year university lecture hall under the guidance of a professor. All students in one class and their teacher are involved in this study. The gathered information pertains solely to the tasks and the students’ evaluations.Findings: Based on the findings of this study, it appears that CT can be taught as a supplementary topic within the framework of a predetermined curriculum. Students’ lists of challenges to CT development and use and assertions that multiple techniques were related to CT development corroborated previous statements in CT research. According to student reports, they are changing their ways of thinking and evaluating aid strategies.Implications/Novel Contribution: To better understand the differences between the experimental and control groups, it would be helpful to conduct additional experiments with these students. One-half of the course experienced interference, while the other half did not. Examining the two groups’ CT skills might shed light on whether or not the knowledge was retained.